PHASE ANALYSIS AND PHYSICAL PROPERTIES OF B2O3-ADDED ZIRCON CERAMICS SINTERED AT 1300 °C - Fikriyatul Azizah Su'ud; Suminar Pratapa; Musyarofah Musyarofah (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2021)
This study was aimed to know the effect of B2O3(boria) addition on the phase composition and physical properties of zircon ceramics.The raw zircon powder used in the study was a purified natural zircon sand from Kereng Pangi, Central Kalimantan, Indonesia. The zircon ceramics were prepared by a solid state reaction method with variation of B2O3 addition of 3 wt%, 6 wt% and 9 wt% and sintered at 1300 °C for 5h. The phase composition, density and microstructure were characterized using X-ray diffraction (XRD), densimeter and Scanning Electron Microscope (SEM), respectively. Vickers Hardness measurement was perfomed at the polished surface of the ceramics. Results showed that all samples contained pure zircon phase, i.e. there was no effect of B2O3 addition on the phase composition. In general, the density and hardness increased with increasing B2O3 addition, but addition up to 9 wt% is not optimum to achieve ultra-dense zircon ceramics. Furthermore, the SEM image also showed no significant difference in average grain size. The crystallite size has grown nearly eight times (325 nm) of its original powder. The Vickers hardness of the ceramics is not significantly influenced by the addition of boria. It appears that the boria failure to increase densification also results in the extent of contact between grains which then produces relatively large zircon grains.